Direct and indirect relevant knowledge: Strategies for handling diversity and unity in teacher education - Fuglseth, Kåre (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This article examines the Norwegian curriculum through neoconservative and neoliberal perspectives, arguing that it represents a confusing hybrid of the two. It proposes two ways to address such hybrids: first, by rethinking the role of knowledge for teaching, and second, by revisiting key Bildung concepts. These concepts shed light on fundamental pedagogical challenges concerning (a) the relationship between formal and material learning and (b) the formation of value categories, such as autonomy and responsibility. The article concludes by emphasizing a crucial distinction in teacher education when guiding future teachers: the difference between indirectly and directly relevant knowledge and skills. Without a clear understanding of relevance, teacher education risks failing in its core mission.